2009
DOI: 10.1113/jphysiol.2009.170431
|View full text |Cite
|
Sign up to set email alerts
|

TRPC channels function independently of STIM1 and Orai1

Abstract: Recent studies have defined roles for STIM1 and Orai1 as calcium sensor and calcium channel, respectively, for Ca 2+ -release activated Ca 2+ (CRAC) channels, channels underlying store-operated Ca 2+ entry (SOCE). In addition, these proteins have been suggested to function in signalling and constructing other channels with biophysical properties distinct from the CRAC channels. Using the human kidney cell line, HEK293, we examined the hypothesis that STIM1 can interact with and regulate members of a family of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
134
1
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 214 publications
(146 citation statements)
references
References 101 publications
(173 reference statements)
9
134
1
2
Order By: Relevance
“…TRPC1 is also implicated in store-operated calcium entry (25,26), in some cases with ORAI1 (44, 45), so we assessed its potential role in lactation. However, there are contradictory reports of the role of TRPC1 in storeoperated calcium entry (46,47) and our studies show that Trpc1 is unlikely to be associated with the Orai1-mediated calcium influx occurring during lactation, as there was a significant decline in its levels during lactation.…”
Section: Discussionmentioning
confidence: 76%
“…TRPC1 is also implicated in store-operated calcium entry (25,26), in some cases with ORAI1 (44, 45), so we assessed its potential role in lactation. However, there are contradictory reports of the role of TRPC1 in storeoperated calcium entry (46,47) and our studies show that Trpc1 is unlikely to be associated with the Orai1-mediated calcium influx occurring during lactation, as there was a significant decline in its levels during lactation.…”
Section: Discussionmentioning
confidence: 76%
“…This may explain a recent report claiming that TRPC3 and TRPC6 expressed in HEK cells do not function as SOCs 19 and that knockdown of TRPC6 does not affect SOC activity in proliferative vascular smooth muscle cells. 20 when expressed at high levels, both channels showed spontaneous activity that was independent of STIM1.…”
Section: Interaction Of Stim1 With the Trpcsmentioning
confidence: 78%
“…14,[16][17][18] The expression studies generated the most controversy since the findings were not uniform, with several groups reporting that the expressed TRPC channels function as SOCs, 14,[16][17][18] while others using the same expression system concluded that the same TRPC channels do not function as SOCs. 19,20 Several of these differences could be traced to expression level of the channels 16,21 and most likely because several of the TRPC channels can function both in SOC and non-SOC modes (see below).…”
Section: Interaction Of Stim1 With the Trpcsmentioning
confidence: 99%
“…Several studies show that association between TRPC1 and STIM1 increases following store depletion (6,16,19,20), although a recent study was unable to demonstrate this (21). While the ezrin/radixin/moesin (ERM) domain of STIM1 appears to bind to TRPC1, the C-terminal 684 KK 685 residues are involved in gating the channel via electrostatic interaction with TRPC1( 639 DD 640 ) (8,13).…”
mentioning
confidence: 99%